Reliability of focused cardiac ultrasound performed by first-year internal medicine residents at a community hospital after a short training - Sireesha Upadhrasta; Mohamed Hussien Raafat; Ricardo A.S. Conti (Greater Baltimore Medical Center, 2019)
The use of bedside ultrasound over the past few decades has created a new wave of options for visualizing pathological processes allowing for faster and better detection of disease. We aimed to evaluate the reliability of focused cardiac ultrasound (FCU) performed by first-year internal medicine residents at a community hospital after a short period of training. They received a two-hour lecture and initially performed a supervised FCU followed by ten unsupervised/independent FCUs each. The four parameters that were assessed were left systolic ventricular function, right systolic ventricular function, presence of pericardial effusion, and presence of IVC dilation. Interpretation and analysis of ultrasound images were then carried out by both the residents and an attending physician with expertise in FCU analysis and interpretation. Cohen's Kappa values were obtained comparing the results found by the interns versus the attending. Our findings indicate that more training is required for reliable analysis of FCU by first-year medical residents. Our results also emphasize the need to carefully evaluate the medical residents' FCU skills after the training.